Unearthing Causative Factors of Cost Overrun on Ghanaian Road Projects - Opeoluwa Akinradewo; Clinton Aigbavboa; Ayodeji Oke; Harrison Coffie; Babatunde Ogunbayo (The Baltic Journal of Road and Bridge Engineering, 2022)
When determining the success of a road project, cost is one of the most important variables to consider. This is because cost is the project’s backbone and driving force throughout the construction process. As a result, to assess the cost performance of a road project, the actual cost is compared to the planned cost. This research aims at uncovering the causal variables that contribute to cost overruns on road projects using Accra, Ghana as a case study. Relevant literature was thoroughly reviewed to extract identified factors. This study adopted a quantitative research approach, using a questionnaire developed to collect data from the target audience. The questionnaire survey was conducted using civil engineers and quantity surveyors working in the Ghanaian construction sector. The data that were retrieved were analysed using descriptive statistics and exploratory factor analysis. According to the findings, the main reasons driving cost overruns on road projects include consultant/ contractor-related, environment-related, economy-related, risk/uncertainty-related, technical-related, owner/client-related, and other project-related factors. It was determined that cost overruns in construction projects occurred because of a lack of professionalism on the part of the stakeholders engaged in the construction process from start to finish. Future research may therefore be conducted utilising all of Ghana’s regions to obtain a broad view of the research.